Determinan Pemanfaatan Kartu Jaminan Kesehatan Nasional (JKN) di Wilayah Kerja Puskesmas Manutapen Kecamatan Alak Kota Kupang - Helena Doko; Yoseph Kenjam; Enjelita M. Ndoen (Media Kesehatan Masyarakat, 2019)
To achieve Universal Health Coverage (UHC) for the entire population, the Indonesian government took the initiative to establish a public health insurance system through JKN for individual health. The JKN program managed by BPJS, intended to provide health protection for participants to obtain health care benefits and protection to meet the basic health needs. However, the use of JKN cards in community health centers (Puskesmas) remains low. This study was to investigate the determinants of JKN card utilization in Puskesmas Manutapen in 2019. The research is was quantitative study using a cross-sectional design. The sample consisted of 85 people obtained by a purposive sampling technique. Data analysis employed using univariate and bivariate methods with the chi-square test. The results showed that factors related to JKN card utilization were knowledge (ρ =0.023), income (ρ = 0.037), the availability of facilities and infrastructure (ρ = 0.043), and disease complaints (ρ = 0.041), while unrelated factor was family support (ρ= 0.662). The community should maximize the use of JKN card to obtain comprehensive health services, not only for treatment, but also for prevention to improve their health status. To achieve Universal Health Coverage (UHC) for the entire population, the Indonesian government took the initiative to establish a public health insurance system through JKN for individual health. The JKN program managed by BPJS, intended to provide health protection for participants to obtain health care benefits and protection to meet the basic health needs. However, the use of JKN cards in community health centers (Puskesmas) remains low. This study was to investigate the determinants of JKN card utilization in Puskesmas Manutapen in 2019. The research is was quantitative study using a cross-sectional design. The sample consisted of 85 people obtained by a purposive sampling technique. Data analysis employed using univariate and bivariate methods with the chi-square test. The results showed that factors related to JKN card utilization were knowledge (ρ =0.023), income (ρ = 0.037), the availability of facilities and infrastructure (ρ = 0.043), and disease complaints (ρ = 0.041), while unrelated factor was family support (ρ= 0.662). The community should maximize the use of JKN card to obtain comprehensive health services, not only for treatment, but also for prevention to improve their health status.